Stop Thinking: An Experience Sampling Study on Suppressing Distractive Thoughts at Work - Niessen, Cornelia; Göbel, Kyra; Lang, Jonas W. B.; Schmid, Ute (Frontiers in Psychology, 2020)
In modern work environments, it can be difficult for workers to avoid becoming distracted from their current task. This study investigates person-situation interactions to predict thought control activities (kind of self-control), that aim to stop distracting thoughts that enter the mind. Specifically, it was examined (1) how challenging work demands (time pressure, task complexity) activate workers’ thought control to stop distractive thoughts (nlevel2 = 143) and relate to the effort to do so (nlevel2 = 91) in daily working life, and (2) how these relationships differ according workers’ general cognitive ability to suppress unwanted thoughts. To understand these person-situation interactions an experience sampling study was combined with a laboratory task assessing the ability to suppress unwanted thoughts (think/no-think task). Multilevel modeling revealed that workers’ engage more often and more intensively in thought control activities at a moderate level of time-pressure, but only when they had a higher general ability to suppress unwanted thoughts. For workers with a lower ability to suppress unwanted thoughts, increasing time pressure was negatively related to thought control activities, even at very low levels of time pressure. Thus, whether time pressure activates or hinders thought control depends on individuals‘ ability to suppress distractive thoughts.